RETRACTED: Techniques for the formation of the natural and ecological framework of riverine cities (on the example of Rostov-on-Don) - Vorob’yova A.M. (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 84, 00001 (2024), https://doi.org/10.1051/bioconf/20248400001